SOCIAL ECONOMY DIMENSIONS FROM ROMANIA. PERSPECTIVES AND REALITIES OF NGO SECTOR - FELICIA ANDRIONI; MIHAELA CAMELIA SCHMIDT (Annals of the University of Petrosani: Economics)
Beginning with 2000 European Union understood the importance of a new perspective for European community: Social Economy. Social economy refers to individuals or legal entities who come together to take on an active economic role in the social inclusion. Social Economy represents the activities and services income generating to help vulnerable people to integrate on the labor market. In this article, in the theoretical part after we are presenting some social economy conceptual delimitations, are highlighted some dimensions of social economy in Romania, and also we analyze the actual situation and the role of the social economy for NGO sector. Our descriptive analyze used the following research methods: analysis documents, comparative analysis.